Microstructure Effects on the Machinability of AM-Produced Superalloys - Paul Wood; José Díaz-Álvarez; Alexis Rusinek; Urvashi Gunputh; Slim Bahi; Antonio Díaz-Álvarez; Maria Henar Miguélez; Yiling Lu; Pawel Platek; Judyta Sienkiewicz (Crystals, 2023)
This paper discusses the microstructure effects on the machinability of Inconel 718 by conducting machining tests on an additively manufactured (AM) workpiece with a strongly textured grain structure and a wrought workpiece incorporating a finer and more equiaxed grain structure. The AM workpiece was produced as a thin tube using Laser Melting Powder Bed Fusion and optimal processing conditions for this alloy. A lathe was used to conduct instrumented orthogonal machining tests on the two workpiece materials under dry cut and coolant conditions using a semisynthetic emulsion coolant. The process parameters studied were feed from 0.05 to 0.15 mm/rev and cutting speed from 60 to 120 m/min with a cut time of 2 sec duration for each process condition. Measures for each process condition included cutting forces in the feed and main cut direction, and images of chip forms were obtained. The grain structures of the workpiece materials were characterized using Electron Back Scattered Diffraction (EBSD). New findings suggest that grain structures can significantly affect the machinability of the superalloy at a higher feed for all cutting speeds studied, and insights into the cause are discussed. Other important findings comment on the effectiveness of the coolant as a lubricant for reducing friction in machining.